Diversidade bacteriana ruminal e digestão in vitro de dietas de alto concentrado para bovinos de corte terminados intensivamente a pasto - Mombach, Mircéia Angele (2020)
There are several commercial additives on the market that have been used for ruminants to reduce the incidence of digestive and metabolic disorders and to improve animal performance on high-concentrated diets. Thus, we hypothesize that the association of these additives in intensive finishing systems in pasture can alter the digestive parameters by modifying the rumen microbiome, reducing gas production, and favoring the degradation of cell wall components, with an effect on the health of the animal. In this sense, two experiments were carried out to evaluate the effects of the association of additives in the diet of beef cattle on the abundance of some species of bacteria and rumen protozoa and fermentative parameters. In both experiments, four types of supplements were evaluated: urea (U), slow-release non-protein nitrogen (U+SRN), yeast (Saccharomyces cerevisiae; U+SRN+Y) and; bacterial probiotics (live strains of bacteria; U+SRN+Y+BP). In addition to the additives, all supplements contained salinomycin and virginiamycin. In the first experiment, supplements were daily offered to animals at a ratio of 17.5 g kg-1 of body weight for 98 days. Samples of ruminal content (solid and liquid) from supplemented animals were collected after slaughter to quantify groups of fibrolytic bacteria (Ruminococcus albus and Fibrobacter succinogenes), non-fibrolytic (Prevotella ruminicola, Selenomonas ruminantium, and Streptococcus bovis), total methanogenic and ciliate protozoa, using qPCR. These samples were compared to a group of animals kept on pasture, but that did not receive supplementation (control). For animals that received supplementation, the abundance of S. bovis decreased by 90% compared to the control. The inclusion of yeast (U+SRN+Y) increased the amount of F. succinogenes and the group of fibrolytic bacteria by 2.2-fold and the population of protozoa by 50%. The association of all additives (U+SRN+Y+BP) increased the abundance of P. ruminicola and the group of non-fibrolytic bacteria about the animals in the control group. In the second experiment, diets with 80% concentrate were evaluated by the in vitro gas production technique to determine fermentation parameters after 48 h of incubation. The estimated final gas volume was higher for the U+SRN+Y diet (159 ml g MS-1 ), but with a lower rate of degradation (0.07% h-1 ). The U+SRN+Y+BP diet increased by 5, 8.5, and 17.5%, respectively, the in vitro digestibility of dry matter (IVDMD), neutral detergent fiber, and the fiber degradation partition factor compared with other diets. The associated use of yeast and bacterial probiotics in the diet of beef cattle changes the ruminal bacterial diversity, stimulating the growth of fibrolytic bacteria, in addition to increasing IVDMD and degradation efficiency, which can reduce losses with gas emissions.